Social circumstances in Slovenia according to selected elements - Drozg, Vladimir (Journal for Geography, 2015)
The paper shows some characteristics of social structure of Slovenia. The elements of social structure are discussed in four groups: vitality of population, social infrastructure, material wealth of population and social vulnerable social groups. The situation in discussed areas is not very promising. The population is ageing rapidly; the trends of demographic growth are not favourable because the number of people is growing due to immigration and not due to natural growth; social inequality is growing, social systems prevent social collapse; budget expenditures in the future will show the most severe cuts into social activities while regional differences will not decrease but rather the opposite. The number of people risking poverty has been increasing, so are the numbers of recipients of social support.